Public Relations' Role in Promoting Religious Programs at Samarinda Islamic Center Mosque - Adelia, Dina Resa; Nur Hayati, Afita; Saputranur, Saputranur; Malik, Ashrun Mubarak (PT Agung Media Publisher, 2024)
The mosque holds a significant role in Islamic culture, serving not only as a place of worship but also as a center for social, political, and cultural activities. Historically, mosques have functioned as venues for education and strategic planning, as seen during the time of the Prophet Muhammad. The Samarinda Islamic Center Mosque, an icon of Islamic culture in East Kalimantan and the second-largest mosque in Southeast Asia, embodies this multifunctionality. This study aims to explore the role of public relations in publicizing and promoting religious programs at the Samarinda Islamic Center Mosque and to identify the media utilized for these efforts. Employing a qualitative descriptive method, data were collected through observation, interviews, and documentation. A total of 15 informants participated, including 8 public relations staff selected through purposive and snowball sampling techniques and 7 congregation members and visitors chosen via accidental sampling. Data analysis involved condensation, presentation, and conclusion, with validation ensured through interview recordings and photographic evidence. Findings indicate that public relations play a vital role in coordinating program publications and promotions. This includes regular meetings, collaboration with various media outlets, and the use of social media platforms such as Facebook, YouTube, and websites. Additionally, electronic media like radio and television, as well as traditional materials like banners and posters, are employed to maximize outreach and engagement.